Response to PD1 inhibition in conventional chondrosarcoma. Issue 1 (25th September 2018) - Wagner, Michael J.; Ricciotti, Robert W.; Mantilla, Jose; Loggers, Elizabeth T.; Pollack, Seth M.; Cranmer, Lee D.
Abstract : Background: Chondrosarcoma is one of the most common malignant bone tumors in adults. Conventional chondrosarcoma represents around 85% of all chondrosarcomas and is notoriously difficult to treat with chemotherapy. Case presentation: We describe a 67-year-old man with metastatic conventional chondrosarcoma who was treated with nivolumab. Treatment was discontinued after restaging showed increased tumor burden, which later proved to be pseudoprogression. The patient restarted nivolumab and continues to have a near complete response. Conclusion: Conventional chondrosarcoma may be sensitive to checkpoint inhibitors. Further, this case demonstrates clearly the phenomenon of pseudo-progression in this disease, a factor that must be considered in the design of clinical trials and clinical care. This case supports additional study of immunomodulatory agents in this deadly disease.